Research on the Impact of Landscape Planning on Visual and Spatial Perception in Historical District Tourism: A Case Study of Laomendong - Lingfang Shao; Pengfei Ma; Zijin Zhou (Land, 2024)
Exploring the impact of landscape planning on visual and spatial perception is particularly significant for historical district tourism. The existing literature offers limited insight into which historical landscapes most effectively influence tourists’ visual and spatial perceptions. Our study investigates this relationship within the cultural heritage context of Laomendong, a historical district in Nanjing, China. Utilizing the Stimulus–Organism–Response (SOR) theoretical framework, this research explored how the stylistic, symbolic, and spatial dimensions of historical landscapes influence tourists’ visual and spatial perceptions. Structural equation modeling (SEM) was used to test hypotheses concerning the relationships between historical landscapes, visual perception, spatial perception, and individual predispositions. The findings revealed that stylistic factors (material, color, and ornament), symbolic factors (landmark, relic, and sign), and spatial factors (openness, scale, and layout) significantly enhance visual perception and subsequently spatial perception. Visual perception plays a mediating role in the influence of historical landscapes on spatial perception. Individual predispositions, like sensation-seeking, intensify spatial perception, while destination familiarity surprisingly shows a negative effect, suggesting that over-familiarity might diminish the novelty and excitement of a spatial experience. These insights provide practical implications for the sustainable development of landscape planning in historical district tourism.